2015
DOI: 10.1177/0023677215577038
|View full text |Cite
|
Sign up to set email alerts
|

The effect ofSyphacia murison nutrient digestibility in laboratory rats

Abstract: This study was carried out to investigate how pinworm infection in rats affects nutrient digestibility in the hosts. Twenty-four male outbred Wistar rats were randomly divided into two groups of 12 rats each. The rats from the first group (GI) were kept in cages with bedding containing pinworm eggs, and the second (control) group (GII) were kept in a separate room in clean, uncontaminated filter-top cages. The animals were put into individual metabolic cages later. Metabolic trials lasted five days and records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…In a survey in 2006, respondents from 35 US research institutions reported S. muris in 17% of mouse colonies and 42% of rat colonies ( 33 ). Although S. muris is considered non-pathogenic, S. muris infections have been shown to exert significant negative effect on digestibility of nutrients and consequently growth of laboratory rats, which could interfere with experiment outcomes ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a survey in 2006, respondents from 35 US research institutions reported S. muris in 17% of mouse colonies and 42% of rat colonies ( 33 ). Although S. muris is considered non-pathogenic, S. muris infections have been shown to exert significant negative effect on digestibility of nutrients and consequently growth of laboratory rats, which could interfere with experiment outcomes ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological investigations displayed that S. muris caused some alterations, including atrophy and distortion of villi, resulting in the loss of the normal appearance of the intestinal layers. On the same line, Plachý et al 1 found that a high pinworm burden caused histological changes in intestinal layers. Also, Anwar et al 62 detected degenerations of the intestinal mucosa and atrophy of the villi of the terrestrial rodent Psammomys obesus due to helminthic infection.…”
Section: Discussionmentioning
confidence: 85%
“…Syphacia muris is the most prevalent pinworm in laboratory rats, and even under well-managed conditions, it is extremely difficult to keep them free of infection 1 . In addition to its zoonotic ability, they can affect the outcome findings 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Only one out of 13 laboratory mice colonies in animal facilities in Brazil was found to be negative for pinworms (Bicalho et al, 2007). Although non-pathogenic, pinworms compromise the host's growth, haemopoiesis (Burgarski et al, 2006), nutrient digestibility (Plachỳ et al, 2016), and intestinal electrolyte transportation (Philpott et al, 1992). Parasitized animals are commonly subclinical, and affect their physiology, immunology, and biochemical parameters which influence the experimental model (Bicalho et al, 2007).…”
Section: Discussionmentioning
confidence: 99%